2012
DOI: 10.1088/0957-4484/24/3/035703
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substrate nitridation temperature on epitaxial alignment of GaN nanowires to Si(111) substrate

Abstract: An arrangement of self-assembled GaN nanowires (NWs) grown by plasma-assisted molecular beam epitaxy on a Si(111) substrate is studied as a function of the temperature at which the substrate is nitridized before GaN growth. We show that the NWs grow with the c-axis perpendicular to the substrate surface independently of nitridation temperature with only a slight improvement in tilt coherency for high nitridation temperatures. A much larger influence of the substrate nitridation process on the in-plane arrangem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 46 publications
(63 reference statements)
9
67
0
Order By: Relevance
“…8(a) GaN growth. This is in agreement with findings for plasma-assisted MBE growth of similar GaN nanorods grown on Si(111) at high temperature, where an oriented crystalline $2 nm-thick nitrided layer, formed prior to growth, was shown to induce the azimuthal orientation of the nanorods [31,33,34]. It was furthermore shown that an amorphous nitrided layer of equal thicknes did not induce any in-plane orientation of the subsequently grown GaN nanorods.…”
Section: Resultssupporting
confidence: 91%
“…8(a) GaN growth. This is in agreement with findings for plasma-assisted MBE growth of similar GaN nanorods grown on Si(111) at high temperature, where an oriented crystalline $2 nm-thick nitrided layer, formed prior to growth, was shown to induce the azimuthal orientation of the nanorods [31,33,34]. It was furthermore shown that an amorphous nitrided layer of equal thicknes did not induce any in-plane orientation of the subsequently grown GaN nanorods.…”
Section: Resultssupporting
confidence: 91%
“…3(d), the diffracted X-ray beam intensity distributions are located in the center of the pole figure, which indicates that the c-axis of most of the AlGaN nanowires is perpendicular to the substrate and agrees with the θ-2θ scan result. 64,65 Moreover, a distribution of the tilt angles of the AlGaN nanowires with the [0002] axis is also expected because of the rough substrate surface. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to nanowire nucleation, the Si substrate is nitridated by the N plasma inducing the formation of an amorphous SiN x interlayer. Nevertheless, the in-plane orientation of the nanowires clearly follows that of the Si(111) substrate with a deviation (twist) of about 3 • [20,29]. To simplify the calculations below and to preserve a symmetric shape of the nanowires, we assume that relaxation at the interface proceeds in the same way as at the joints.…”
Section: Energy Of the Dislocation Networkmentioning
confidence: 99%